A uniQue wAy of Transcatheter mAss extraction - Mhd Baraa Habib, MD; Shabib AlAasmy, MD; Cheikh Ahmed Aboulmaaly, MD; Hakam Alzaeem, MD; Nazar Mohammed, MD; Mohammed Al-Hijji, MD; Mohammed Qintar, MD, MSc (JACC: Case Reports, 2025)
Background: Intracardiac masses traditionally require surgical resection, but transcatheter techniques offer a less invasive alternative. Case Summary: A 57-year-old woman with rheumatic heart disease and severe mitral stenosis was evaluated for percutaneous mitral commissurotomy. Imaging revealed a mobile right atrial mass near the inferior vena cava, posing a risk for embolization. Given the need for mass removal before the procedure, we performed the QATAR technique using the Penumbra Lightning 16 system, a loop snare, and electrocautery. The mass was successfully extracted without complications. Discussion: This case highlights the feasibility of a novel transcatheter approach for intracardiac mass removal, reducing the need for open surgery. The QATAR procedure integrates electrosurgery with catheter-based extraction, expanding therapeutic options for high-risk patients. Take-Home Messages: We aim to highlight a novel transcatheter technique combining electrosurgery and catheter-based therapies to remove intracardiac tumors. The QATAR procedure is a safe and effective technique for intracardiac mass removal, offering a minimally invasive alternative to surgery.